2013
DOI: 10.1080/08870446.2013.863883
|View full text |Cite
|
Sign up to set email alerts
|

Making concrete construals mindful: A novel approach for developing mindfulness and self-compassion to assist weight loss

Abstract: Research on the usefulness of mindfulness and self-compassion for dieting has focused on meditative practices. However, meditation can be difficult to maintain, especially while dieting. Thus, the present research attempted to induce mindfulness and self-compassion by using food diaries that required the participant to either focus on concrete (i.e. how they are eating) construals or abstract (i.e. why they are eating) construals. The concrete construals were expected to increase mindfulness and self-compassio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
172
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(175 citation statements)
references
References 51 publications
(67 reference statements)
2
172
1
Order By: Relevance
“…(p. 142). Furthermore, the items reflecting mindful awareness within the scale are similar to questions used in a recent intervention that proved to be successful for weight loss [13]. Future research should explore these findings further with better physiological measurements, and more specific measurements of consumption.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…(p. 142). Furthermore, the items reflecting mindful awareness within the scale are similar to questions used in a recent intervention that proved to be successful for weight loss [13]. Future research should explore these findings further with better physiological measurements, and more specific measurements of consumption.…”
Section: Discussionmentioning
confidence: 93%
“…A negative relationship was found between mindfulness and BMI in a recent population study with French adults (N=63.628) [8]. Furthermore, people who eat more mindfully, or participate in mindfulness meditation programmes have been found to improve the way they eat and successfully eat less [9][10][11][12][13][14]. However, Mantzios and Wilson [13] suggested that the combination of mindfulness and self-compassion might be more beneficial than mindfulness alone, and this was subsequently evidenced in other studies [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social marketing typically faces the challenge of promoting concrete behaviour that corresponds to abstract goals that are socially desirable (Rothschild, 1979) in a context where socially undesirable behaviour comes naturally. The majority of research in social marketing focuses on raising the construal level of actual choices by awareness and self-control in order to decrease the influence of low construal incentives or 'guilty pleasures' (Amel et al, 2009;Fujita, 2011;Fujita & Roberts, 2010;Mantzios & Wilson, 2014;Wieber, Sezer, & Gollwitzer, 2014). Awareness raises the relevance, but not necessarily the determinance of distal goals or goal congruent attributes.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this approach cognitive interventions aim at inducing abstraction and mindfulness to raise the construal level of the proximal choice and thus enhance the motivation for distal-goal-congruent behaviour, or to raise the self-control to resist goal-incongruent temptations (Amel, Manning, & Scott, 2009;Fujita & Roberts, 2010;Jenkins & Tapper, 2014;Mantzios & Wilson, 2014). A major drawback of these cognitive interventions is that they require effort and energy of the actor that are subject to depletion (Agrawal & Wan, 2009;Gino, Schweitzer, Mead, & Ariely, 2011;Imhoff, Schmidt, & Gerstenberg, 2015;Muraven & Baumeister, 2000).…”
Section: Coping With Construal Conflictsmentioning
confidence: 99%